Pengaruh Perbandingan Rasio Tepung Kentang dan Tepung Tapioka Serta Penambahan Bubuk Daun Kersen (Muntingia calabura) Pada Mie Basah Non Gluten - Handayani, Anna Mardiana; Citra Kusumasari, Findi; Setyowati, Lisus; Nurul Satya, Malinda Capri (Universitas Trunojoyo Madura, 2024)
This study aims to determine the effect of the ratio of potato flour and tapioca flour and addition of kersen leaves powder on gluten-free wet noodles with a focus on proximate levels (water, ash, protein, fat, and carbohydrate content by different) and antioxidant activity (DPPH method). The research design used was a RAK with two factors. The first factor was the ratio of potato flour and tapioca flour and the secondly was the variation of kersen leaves concentration, which consist of 3 treatment levels respectively, so it’s obtained 9 samples with 2 replications. The data were processed using the ANOVA test and if there was a significant difference, then continue with the DMRT test (significance level 5%). The results showed that the effect of the ratio of potato flour and tapioca flour had an effect on increasing water content, protein content and reducing on carbohydrate content while ash content and fat content did not have a significant effect. Non-gluten wet noodles had antioxidant activity of around 36.2-52.5%. The increased of the concentration of kersen leaves powder so the antioxidant activity as well as increased. Further research is still needed to examine the potential of our functional food products such as antidiabetic and antihypercholesterol using in vivo studies. Also, the isolation of bioactive components of kersen leaves using nanotechnology to make them easier to be absorbed by the body.